Integrative Mapping of Phytochemistry, Pharmacology, Green Extraction, and Bioeconomics Peperomia pellucida (L.) Kunth: Systematic Literature Review - Subakir Salnus; Ayu Sri Wiyanti; Hardianti Rahman; Yusran Katarina; Wisye Riska Leleallo Sura'; Andi Bau Andriwati (Hayyan Journal, 2026)
This study aims to integrate scientific evidence on phytochemistry, pharmacology, green extraction, and bioeconomics of Peperomia pellucida (L.). Kunth through the Systematic Literature Review approach. The research was conducted by searching the Scopus database for articles using keywords related to Peperomia pellucida, phytochemicals, pharmacology, extraction, toxicology, antioxidants, antibacterial activity, and antidiabetic activity. Of the initial 89 articles, the selection process across identification, screening, eligibility, and inclusion yielded 34 articles for narrative analysis. The study found that P. pellucida contains various bioactive compounds, including flavonoids, alkaloids, tannins, saponins, phenols, terpenoids, steroids, lignans, phenylpropanoids, essential oils, dillapiole, quercetin, apigenin, stigmasterol, and fucosterol. The compound exhibits antioxidant, anti-inflammatory, antidiabetic, antibacterial, antihypertensive, anticancer, gastroprotective, neuroprotective, antiarthritis, antimalarial, and wound-healing activities. Extraction techniques such as maceration, solvent fractionation, MAE, IL-MAE, NADES, fermentation, drying, and gamma irradiation have been shown to affect compound content, biological activity, safety, and extract quality. This study concludes that P. pellucida has the potential to be developed as an ingredient in herbs, functional foods, phytopharmaceuticals, cosmetics, topical products, bioaccharicides, and bioeconomic commodities, but still requires standardization, safety validation, and further research.